OP0048 TYPE I INTERFERON EXPRESSION IDENTIFIES DIFFERENT SUBSETS OF ANTIPHOSPHOLIPID SYNDROME. (2nd June 2020) - Cecchi, I.; Radin, M.; Rubini, E.; Foddai, S. G.; Suárez, A.; Sciascia, S.; Roccatello, D.; Rodríguez-Carrio, J.
Abstract : Background: Type I Interferons (IFN) play a key role in the pathogenesis and development of various autoimmune conditions. Among them, a solid amount of data demonstrates that the expression of various IFN regulated genes (IRGs), the so-called "IFN signature", has been linked to disease activity and disease progression in systemic lupus erythematosus (SLE) patients. Nevertheless, to date, a limited number of studies have analysed the IFN signature in antiphospholipid syndrome (APS) setting. Objectives: This study aims to describe the activation and structure of the type I IFN signature among different subsets of APS, including primary APS (PAPS) and when associated with other autoimmune conditions (secondary APS - SAPS), and antiphospholipid antibodies positive individuals ("aPL carriers"). Methods: A total of 116 patients were enrolled, including 19 PAPS patients, 13 SAPS, 75 SLE patients, and 9 aPL carriers [1, 2]. Thirty-two subjects were also recruited as healthy controls (HCs). IFI44, IFI44L, IFI6, MX1 and IRF4 gene expression was determined in whole blood in the entire cohort. Expression levels were normalized to Z-scores and averaged into a global IFN signature. Differences were measured by Kruskal-Wallis tests and associations among genes were studied by cluster and correspondence analyses. Correlations were plotted by network analyses. Results: A global activation of the type I IFN signature was observed (HCs: -0.44±0.08, aPL carriers: -0.38±0.12, PAPS: -0.31±0.80, SAPS: -0.17±0.39, SLE: 0.09±0.80; p(Kruskal-Wallis)< 0.001). A certain degree of heterogeneity was observed among IRGs: MX1 being increased in all patient groups (all p< 0.001), whereas IFI44 was only increased in SLE (p< 0.001) and PAPS (p< 0.001), and both IFI44L and IFI6 were increased in SLE (both, p< 0.001) and a trend was observed in SAPS (p=0.060 and p=0.080) (Figure 1 ). By means of an unsupervised analysis, 3 clusters (I to III) were identified, which correlated with clinical status of the patients by correspondence analysis (p< 0.0001, Figure 2a ). Network analyses revealed different structures of the IRGs networks among groups, from weaker networks in HCs and aPL carriers to stronger degree of correlations among IRGs in SAPS and SLE, thus pointing to diverse expression programs (Figure 2b ). Among APS patients (both SAPS and PAPS), the IFN signature was positively associated with anti-phosphatidylserine/prothrombin antibodies IgG levels (r=0.478, p=0.003), but no associations were observed for the IgM isotype nor with other autoantibodies specificities (all p >0.050). No associations were observed with traditional cardiovascular risk factors or current treatments (all p >0.050). Conclusion: In line with other autoimmune conditions, APS is associated with a broad type I IFN activation, with distinct profiles of the IFN signature structure among different clinical subsets, suggesting that different pathogenic pathways are involved in the pathogenesis of these conditions. References: [1]Miyakis S, et al. J Thromb Haemost (2006); [2] Aringer M, et al. Arthritis Rheumatol (2019). Acknowledgments: None Disclosure of Interests: None declared